Pengaruh Kompetensi dan Penggunaan Teknologi pada SDM terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening di Inspektorat Daerah Kabupaten Solok - Intan Verozia; Marta Widian Sari; Harmelia Harmelia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the test results of the influence of competence and the use of technology on human resources on employee performance with job satisfaction as an intervening variable at the Inspektorat Daerah Kabupaten Solok. Research is descriptive quantitative. The sample used was 35 employees. Instrument tests use validity tests and reliability tests. The analysis method used is Structural Equation Modeling (SEM) with SmartPLS version 0.3. The results of this study indicate that: Competence has a positive and significant effect on Job Satisfaction, The use of technology has a positive effect on job satisfaction, Competence has a positive and significant effect on Employee Performance, The use of technology has a positive effect on employee performance, Job Satisfaction has a positive effect on Employee Performance, Competence has a positive effect on Employee Performance through Satisfaction, Use of Technology has a positive effect on Employee Performance through Job Satisfaction.